DETECTION OF POWER TRANSFORMER FAULTS USING DGA BASED ON COMBINED DUVAL PENTAGON AND ANN CLASSIFIERS (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2026)
Starting from the need to reduce the time required to analyze and detect power transformer faults, this article presents a software application specific to this topic, based on Artificial Neural Network (ANN) classifiers, in which the theoretical analysis method is Duval Combined Pentagons (DCP). The software application is based on algorithms implemented in Classification Learner from the MATLAB Statistics and Machine Learning toolbox. The classifiers' accuracy is optimized using Bayesian search, Grid search, and Random search. The developed software application was validated through several case studies, two of which were presented in comparison with the maintenance work performed.
Keywords: Remove Dissolved Gas Analysis (DGA); Diagnostics